DRD2 methylation is associated with executive control network connectivity and severity of alcohol problems among a sample of polysubstance users - Hagerty, Sarah L.; YorkWilliams, Sophie L.; Bidwell, L. Cinnamon; Weiland, Barbara J.; Sabbineni, Amithrupa; Blaine, Sara K.; Bryan, Angela D.; Hutchison, Kent E. (Addiction biology, 2020)
Chronic exposure to alcohol and other drugs of abuse has been associated with deleterious consequences, including functional connectivity deficits within neural networks associated with executive control. Altered functional connectivity within the executive control network (ECN) might underlie the progressive inability to control consumption of alcohol and other drugs as substance use disorders progress. Genetic and epigenetic factors have been associated with substance use disorders (SUDs). For example, dopamine receptor 2 (DRD2) functioning has been associated with alcohol use disorder (AUD) and related phenotypes, including correlates of executive functioning. The present study aims to explore the relationship between a continuous measure of alcohol‐related problems, epigenetic markers (methylation) within the DRD2 gene, and functional connectivity within the ECN among a sample of polysubstance users. A community sample of 658 subjects, whose consumption of alcohol, nicotine, and cannabis span across a spectrum of quantity and frequency of use, were obtained across previous studies in polysubstance using populations. Resting state functional magnetic resonance imaging was analyzed to identify intrinsic connectivity networks using a priori regions of interest. Methylation measurement of functionally relevant sites within the DRD2 gene was achieved via pyrosequencing. Regression‐based models, including mediation and moderation models, tested the association between DRD2 methylation, functional connectivity within intrinsic neural networks (including the ECN), and severity of alcohol problems. Results suggest that average DRD2 methylation was negatively associated with right ECN (RECN) and left ECN (LECN) connectivity, but not associated with other networks tested, and DRD2 methylation was significantly associated with alcohol problems severity. Mediation models were not supported, although moderation models suggested that connectivity between edges within the RECN moderated the relationship between DRD2 methylation and AUD severity. Results support a theoretical model in which epigenetic factors are associated with neurobiological correlates of alcohol consumption among a sample of polysubstance users. The figure depicts a working model of the role of epigenetics in neural network changes in response to chronic alcohol consumption. The current investigation provides cross‐sectional evidence that severity of alcohol problems is associated with DRD2 methylation in the periphery, which is in turn associated with decreased executive control network connectivity among a sample of polysubstance users.